Twelve year interannual and seasonal variability of stream carbon export from a boreal peatland catchment. Issue 7 (13th July 2016) - Leach, J. A.; Larsson, A.; Wallin, M. B.; Nilsson, M. B.; Laudon, H.
Abstract: Understanding stream carbon export dynamics is needed to accurately predict how the carbon balance of peatland catchments will respond to climatic and environmental change. We used a 12 year record (2003–2014) of continuous streamflow and manual spot measurements of total organic carbon (TOC), dissolved inorganic carbon (DIC), methane (CH4 ), and organic carbon quality (carbon‐specific ultraviolet absorbance at 254 nm per dissolved organic carbon) to assess interannual and seasonal variability in stream carbon export for a peatland catchment (70% mire and 30% forest cover) in northern Sweden. Mean annual total carbon export for the 12 year period was 12.2 gCm −2 yr −1, but individual years ranged between 6 and 18 gCm −2 yr −1 . TOC, which was primarily composed of dissolved organic carbon (>99%), was the dominant form of carbon being exported, comprising 63% to 79% of total annual exports, and DIC contributed between 19% and 33%. CH4 made up less than 5% of total export. When compared to previously published annual net ecosystem exchange (NEE) for the studied peatland system, stream carbon export typically accounted for 12 to 50% of NEE for most years. However, in 2006 stream carbon export accounted for 63 to 90% (estimated uncertainty range) of NEE due to a dry summer which suppressed NEE, followed by a wet autumn that resulted in considerable stream export. Runoff exerted a primary control on stream carbon export from this catchment; however, our findings suggest that seasonal variations in biologic and hydrologic processes responsible for production and transport of carbon within the peatland were secondary influences on stream carbon export. Consideration of these seasonal dynamics is needed when predicting stream carbon export response to environmental change. Key Points: Stream carbon export varied between 6 and 18 gCm −2 yr −1 Stream carbon export accounted for 25 to 90% of annual NEE Seasonal variability in carbon supply and transport influenced export rates